Molecular characterization of Haemaphysalis longicornis tick salivary gland-associated 29-kilodalton protein and its effect as a vaccine against tick infestation in rabbits - Mulenga, A.; Sugimoto, C.; Sako, C.; Ohashi, K.; Musoke, A.J.; Shubash, M.; Onuma, M. (American Society for Microbiology, 1999)
The use of tick vaccines in mammalian hosts has been shown to be the most promising alternative tick control method to current use of acaricides, which suffers from a number of limitations. However, the success of this method is dependent on the identification cloning, and in vitro expression of tick molecules involved in the mediation of key physiological roles with respect to the biological success of a tick as a vector and pest. We have sequenced and characterized a Haemaphysalis longicornis tick salivary gland-associated cDNA coding for a 29-kDa extracellular matrix-like protein. This protein is expressed in both unfed and fed immature and mature H. longicornis ticks. The predicted amino acid sequence of p29 shows high homology to sequences of some known extracellular matrix like-proteins with the structural conservation similar to all known collagen proteins. Immunization with the recombinant p29 conferred a significant protective immunity in rabbits, resulting in reduced engorgement weight for adult ticks and up to 40 and 56 percent mortality in larvae and nymphs that fed on the immunized rabbits. We speculate that this protein is associated with formation of tick cement, a chemical compound that enables the tick to remain attached to the host, and suggest a role for p29 as a candidate tick vaccine molecule for the control of ticks. We have discussed our findings with respect to the search of tick molecules for vaccine candidates.